Laser cladding and thermal spray coatings on steel pipe serving the oil and gas industry. - Almeida, Natália Chaves (2017)
Different coating systems were characterized using a commercial API 5CT steel grade L80 type 1, which is commonly used in the oil and gas industry. Two Ni-based alloys and one Co-based alloy were deposited by laser cladding. Two coatings were deposited (Ni-based alloy and a composite W-C/Co-base) by means of thermal spray process. It has been shown the presence of a hard heat affected zone (HAZ) in the substrate for the as-laser deposited coating. The main explanation for this HAZ is devoted to the heat gradient causing a gradient on the prior austenite grain size and consequently different martensite hardness along the HAZ. For the thermal sprayed coatings, no HAZ was formed due to low heat input process. All the studied coating systems seem to be very interesting for different technically demanding applications, such as, stress sulfide corrosion and wear resistance.